High affinity binding of anti-oestrogen to the chick liver nuclear oestrogen receptor - Lazier, Catherine B. (1982)
Tamoxifen is a potent inhibitor of specific oestrogen-induced yolk protein synthesis by chicken liver. The oestradiol receptor in salt extracts of liver nuclei from oestrogen-treated chicks has a K(d) for oestradiol of 0.7±0.2nm. Tamoxifen and its metabolite, monohydroxytamoxifen, compete for binding to the salt-soluble nuclear receptor with K(i) values of 2.6 and 0.1nm respectively. The anti-oestrogens show much less inhibition of [(3)H]oestradiol binding when assays are carried out using intact nuclei. The competition by unlabelled oestradiol for [(3)H]oestradiol binding to receptor is identical in both salt extracts and intact nuclei. This suggests that intact nuclei contain components which bind anti-oestrogens, but not oestradiol. While tamoxifen and desmethyltamoxifen will readily dissociate from the salt-soluble nuclear oestrogen receptor, monohydroxytamoxifen does not dissociate under the conditions generally used for exchange assays. A modified assay was developed in which 60–70% of monohydroxytamoxifen-bound sites were shown to be exchangeable for [(3)H]oestradiol. Soluble receptor preparations were first incubated in a 1.7% charcoal suspension at 37°C for 15min before assay of specific oestradiol binding. This technique was used in examining the effects of tamoxifen and monohydroxytamoxifen given in vivo on the nuclear oestrogen receptor concentration. Despite their 30-fold difference in binding affinity for the receptor, both anti-oestrogens increase nuclear receptor levels to about the same degree. When given with oestradiol, both compounds have the same apparent partial inhibitory effect on the oestrogen-induced increase in nuclear receptor. These data are consistent with the metabolic hydroxylation of tamoxifen before binding to the hepatic oestrogen receptor.